Anti-hail covers causes changes in the quality and biochemistry in two blueberry (Vaccinium corymbosum L.) cultivars - Luisina Morales; Agustín Gollán; Fernando Bello; María F. Rivadeneira; Daniel Vázquez; Karina E.J. Tripodi (Technology in Horticulture)
Given the increased frequency of hailstorms that pose a threat to blueberry fruit and bushes, the utilization of anti-hail covers has become prevalent in Argentina's North-Eastern region. However, this practice may alter the orchard microclimate, potentially affecting fruit quality. The impact of these covers on the biochemical composition and agronomic attributes of two extensively cultivated blueberry cultivars, 'Emerald' and 'Snowchaser' was investigated. The early phenological stages exhibited a delay of several days in fruit under cover, which could potentially postpone the onset of the commercialization period. Seasonal and varietal variations in phenolic compound levels and cell wall-associated enzyme activity were observed, although these differences were not attributable to the growing conditions. The 'Emerald' cultivar demonstrated an overall positive response to the net application, with measured traits either remaining unaltered or showing improvement in comparison to field growth. The 'Snowchaser' cultivar displayed enhanced firmness when grown under cover, which is a favorable outcome. In this variety, the increase in the levels of raffinose, a stress-related sugar, may indicate a divergence from 'Emerald' with regard to stress sensing. Both varieties demonstrated resistance to decay in the postharvest period, with an increased SS/TA ratio and firmness resulting from the use of covers. Despite some varietal differences, this study supports the efficacy of anti-hail covers in safeguarding blueberries without compromising overall crop health and fruit quality. This outcome is relevant since it validates this practice for two blueberry varieties of commercial importance, thereby reducing the potential loss of fruit and bush damage.